Using Web-Based, Group Communication Systems to Support Case Study Learning at a Distance - Rourke, Liam; Anderson, Terry (International Review of Research in Open and Distributed Learning, 2002)
This study explored the capacity of Web-based, group communication systems to support case-based teaching and learning. Eleven graduate students studying at a distance were divided into three groups to collaborate on a case study using either a synchronous voice, an asynchronous voice, or a synchronous text communication system. Participants kept a detailed log of the time they spent on various activities, wrote a 1,500-word reflection on their experience, and participated in a group interview. Analysis of these data reveals that each group supplemented the system that had been assigned to them with additional communication systems in order to complete the project. Each of these systems were used strategically: email was used to share files and arrange meetings, and synchronous voice systems were used to brainstorm and make decisions. Learning achievement was high across groups and students enjoyed collaborating with others on a concrete task. Keywords: Distance Education, Case-based Learning, Collaboration Software, Online Learning.The evidence in favour of case-based teaching and learning continues to mount (cf. Lundeberg, Levin, and Harrington, 1999). One interesting facet of this research suggests that group discussions are the active ingredient of case study learning. For on-campus students this is simple to arrange, but where does it leave students who are studying at a distance? Case studies are often used in distance education, but traditionally they have been implemented in an independent mode, with students reading a problem-centred or exemplary narrative in order to contemplate its central issues. This type of case-based teaching omits what may be the most important part of case-based pedagogy.Fortunately, a wide array of Web-based communication software exists that supports various types of communication at a distance, including text or voice, person-to-person or multi-person, and synchronous or asynchronous interaction. The relative effectiveness of these systems to support collaboration among students is an important issue to distance educators.